Intense photoluminescence emission at room temperature in calcium copper titanate powders - Moura, F.; Simões, A. Z. [UNESP]; Deus, R. C. [UNESP]; Silva, M. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier, 2013)
A study was undertaken about the structural and photoluminescent properties at room temperature of CaCu3Ti4O12 (CCTO) powders synthesized by a soft chemical method and heat treated between 300 and 800 °C. The decomposition of precursor powder was followed by thermogravimetric analysis (TG-DTA), X-ray diffraction (XRD), Fourier transform infrared (FT-IR), Fourier transform Raman (FT-Raman) and photoluminescence (PL) measurements. XRD analyses revealed that the powders annealed at 800 °C are becoming ordered and crystallize in the cubic structure. The most intense PL emission was obtained for the sample calcined at 700 °C, which is not highly disordered (300-500 °C) and neither completely ordered (800 °C). From the spectrum it is clearly visible that the lowest wavelength peak is placed around 480 nm and the highest wavelength peak at about 590 nm. The UV/vis absorption spectroscopy measurements showed the presence of intermediate energy levels in the band gap of structurally disordered powders. © 2012 Elsevier Ltd and Techna Group S.r.l.
Keywords: A. Ceramics; B. Chemical syntheses; B. Powder metallurgy; C. X-ray diffraction; Calcium copper titanates; Chemical synthesis; Cubic structure; Fourier transform infrared; Fourier transform Raman; FT-Raman; Intermediate energies; Photo-luminescent properties; Photoluminescence emission; Photoluminescence measurements; PL emission; Precursor powder; Room temperature; Soft chemical method; Spectroscopy measurements; Uv/vis absorptions; XRD analysis; Calcination; Photoluminescence; Powder metallurgy; Thermogravimetric analysis; X ray diffraction; Powders